2016
DOI: 10.18172/cig.2934
|View full text |Cite
|
Sign up to set email alerts
|

Variación espacio-temporal de los procesos hidrológicos del suelo en viñedos con elevadas pendientes (Valle del Ruwer-Mosela, Alemania)

Abstract: RESUMEN. Los suelos de los viñedos del valle del Ruwer-Mosela (Alemania)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
3

Year Published

2016
2016
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 70 publications
1
15
0
3
Order By: Relevance
“…The different behavior of the soils in Spain might due to the changes in soil properties triggered by long-term intensive agriculture, which changed the soil properties due to ploughing and the use of pesticides. Agricultural soils in many parts of Spain have been found to be highly degraded, characterized by surface crusting and high soil erosion rates (Taguas et al, 2015;Rodrigo-Comino et al, 2016;Martínez-Casasnovas et al, 2016). The soils in Spain were also enriched in calcium carbonate due to their limestone parent materials and OC levels were not high; therefore, CEC was explained mostly by pH.…”
Section: Discussionmentioning
confidence: 99%
“…The different behavior of the soils in Spain might due to the changes in soil properties triggered by long-term intensive agriculture, which changed the soil properties due to ploughing and the use of pesticides. Agricultural soils in many parts of Spain have been found to be highly degraded, characterized by surface crusting and high soil erosion rates (Taguas et al, 2015;Rodrigo-Comino et al, 2016;Martínez-Casasnovas et al, 2016). The soils in Spain were also enriched in calcium carbonate due to their limestone parent materials and OC levels were not high; therefore, CEC was explained mostly by pH.…”
Section: Discussionmentioning
confidence: 99%
“…The age of the vineyard is also a key factor controlling soil erosion intensity. Rodrigo Comino et al (2015;2016e) observed via botanic benchmarks on recently planted vineyards (approx. 4 yr) a decrease of soil erosion rates from 62.5 Mg ha -1 yr -1 to 33.5 Mg ha -1 yr -1 in two years, whilst the erosion rates on old vineyards (>30 yr) were one order of magnitude lower (decreasing in the same period from 3.4 Mg ha -1 yr -1 to 3.3 Mg ha -1 yr -1 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Southern Germany, vineyards located on steep slopes (between 15 and 50 ) and agricultural terraces (Fischer et al, 1999;Koch et al, 2013) are affected by these soil degradation processes due to the high soil and water losses (Rodrigo Comino et al, 2016d, 2015a, which are influenced by soil compaction, which triggers widespread rill and inter-rill soil erosion losses at high rates (Hacisalihoglu, 2007;Richter, 1980;Rodrigo Comino et al, 2016a,b). The main factors that lead to non-sustainable soil erosion rates are: i) steep slopes; ii) disturbances of the soil profile during the planting of vines (Follain et al, 2012;Johnson et al, 1987); iii) topsoil compaction and decreased soil porosity under heavy machinery wheel traffic (Biarnès et al, 2012;Ferrero et al, 2005); iv) high runoff discharges; and v) tillage practices in the inter-rows.…”
Section: Introductionmentioning
confidence: 99%